(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2021)
Pod grains threshing using mechanical devices is essential in understanding the diversities involved in the application of machine–crop parameter combinations towards achieving best quality grain. The integration of pod grains’ physical properties in optimizing product quality which is vital to meet the increasing global requirement is limited. However, with computing and technological advancements into thresher design and evaluation have been found to be capable of meeting these needs which are of interest to researchers. Over the past three–four decades, the applications of the technology in reducing impact force through modification of peg geometry have attracted researchers’ widespread interest and the future looks promising. This review presents an overview of mechanical thresher development and the applications in the field of pod grain production chain. The role of grain physical properties in threshers design, operations and with force sensors to reveal the mysteries surrounding the causes of grain damage and how they can be minimised are stressed. The current trends and future advances of such studies are also presented.